2014
DOI: 10.1152/japplphysiol.00175.2014
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin administration while maintaining normoglycemia inhibits whole body protein breakdown and synthesis after cardiac surgery

Abstract: We investigated the effect of insulin administered as part of a hyperinsulinemic-normoglycemic clamp on protein metabolism after coronary artery bypass grafting (CABG) surgery. Eighteen patients were studied, with nine patients in the control group receiving standard metabolic care and nine patients receiving insulin (5 mU·kg(-1)·min(-1)). Whole body glucose production, protein breakdown, synthesis, and oxidation were determined using stable isotope tracer kinetics (l-[1-(13)C]leucine, [6,6-(2)H2]glucose) befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Insulin (1) protects against the depletion of glycogen and triglycerides, (2) prevents liver injury by reducing hepatic inflammation, and (3) prevents the phosphorylation of STAT3, thus restoring physiologic hepatic gluconeogenesis 72 . Intensive insulin therapy has demonstrated benefits in select populations, including patients undergoing cardiac surgery and patients with moderate to severe trauma, but benefits in other populations remain unclear 20,26,27,43,62,115,128,134,136,137 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin (1) protects against the depletion of glycogen and triglycerides, (2) prevents liver injury by reducing hepatic inflammation, and (3) prevents the phosphorylation of STAT3, thus restoring physiologic hepatic gluconeogenesis 72 . Intensive insulin therapy has demonstrated benefits in select populations, including patients undergoing cardiac surgery and patients with moderate to severe trauma, but benefits in other populations remain unclear 20,26,27,43,62,115,128,134,136,137 …”
Section: Discussionmentioning
confidence: 99%
“…26,30 The initiation of nutrition support is believed to help with resolution of ebb and flow phases but has not been definitively established. 30,62,63 Notably, some studies have demonstrated that high levels of protein supplementation early in critical illness (presumably during the ebb and flow phases) may be potentially harmful. 64,65…”
Section: Protein Metabolismmentioning
confidence: 99%
“…Past attempts to create anabolism in cardiac surgery with the administration of high-dose insulin alone have been unsuccessful (15). Although insulin can inhibit ubiquitin-proteasome system-induced proteolysis, insulin also causes hypoaminoacidemia and fails to promote protein synthesis in the absence of circulating AA (10,16,22,44).…”
Section: Discussionmentioning
confidence: 99%
“…Blood and expired air samples were collected, before the infusion, to analyze baseline enrichments. The methods used have been previously described in detail (15). Concentrations of glucose, lactate, AA, insulin, cortisol, total protein, albumin, IL-10, IL-1␤, IL-6, IL-8, and TNF-␣ were determined at 150 min of the preand postoperative study period.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation